Use of Gases to Treat Cochlear Conditions - Buckey, Jay C. (Frontiers in Cellular Neuroscience, 2019)
Although the cochlear vascular supply (stria vascularis) is designed to block to certain compounds and molecules, it must enable gas exchange to survive. The inner ear capillaries must deliver oxygen and remove carbon dioxide for the cochlea to function. These gases diffuse through tissues across a concentration gradient to reach the desired target. Tight junctions or the endothelial basement membrane do not impede them. Therefore, gases that can diffuse into the inner ear are attractive as therapeutic agents. The two gases most often used in this way are oxygen and hydrogen, although carbon dioxide, ozone, and argon have also been investigated. Typically, oxygen is delivered as hyperbaric oxygen (oxygen at pressure higher than atmospheric) to provide increased oxygen levels to the inner ear. This not only relieves hypoxia, but also has anti-inflammatory and other biochemical effects. Hyperbaric oxygen is used clinically to treat idiopathic sudden sensorineural hearing loss, and both animal and human studies suggest it may also assist recovery after acute acoustic trauma. Laboratory studies suggest hydrogen works as a free radical scavenger and reduces the strong oxidants hydroxyl radicals and peroxynitrite. It also has anti-apoptotic effects. Because of its anti-oxidant and anti-inflammatory effects, it has been studied as a treatment for ototoxicity and shows benefit in an animal model of cisplatinum toxicity. Gas diffusion offers an effective way to provide therapy to the inner ear, particularly since some gases (oxygen, hydrogen, carbon dioxide, ozone, argon) have important therapeutic effects for minimizing cochlear damage.